2010
DOI: 10.1093/humrep/deq181
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and karyotype analysis of oocytes from patients with polycystic ovary syndrome

Abstract: The chromosomal constitution of in vitro matured oocytes from PCOS is similar to that of controls, but aspects of oocyte metabolism are perturbed by PCOS. Elevated pyruvate consumption was associated with abnormal oocyte karyotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 93 publications
5
43
0
Order By: Relevance
“…The finding of increased plasma lactic acid concentrations in our nonobese patients with PCOS further suggests insulinstimulated glucose uptake and consumption in the muscle of these patients. In conceptual agreement, oocytes from nonobese patients with PCOS show increased glucose and pyruvate consumption during overnight in vitro maturation, a characteristic that is not present in oocytes when patients are treated with the insulin-lowering drug metformin (35 ). These re- Data are m/zRT intensities normalized to internal standard succinic-d4 acid.…”
Section: Discussionmentioning
confidence: 58%
“…The finding of increased plasma lactic acid concentrations in our nonobese patients with PCOS further suggests insulinstimulated glucose uptake and consumption in the muscle of these patients. In conceptual agreement, oocytes from nonobese patients with PCOS show increased glucose and pyruvate consumption during overnight in vitro maturation, a characteristic that is not present in oocytes when patients are treated with the insulin-lowering drug metformin (35 ). These re- Data are m/zRT intensities normalized to internal standard succinic-d4 acid.…”
Section: Discussionmentioning
confidence: 58%
“…Recently, several researchers have reported that melatonin supplementation of the culture medium increased maturation rate, increased receptor expression and reduced reactive oxygen species in porcine and cattle (El-Raey et al, 2011;Kang et al, 2009). Other studies in animal models have suggested that the beneficial effects of melatonin occur through its antioxidant actions against oxidative stress and related damage (AcunaCastroviejo et al, 2001;Combelles et al, 2009;Harris et al, 2010;Requena et al, 2009). This may suggest that melatonin promotes oocyte maturation by binding to its receptor and/or improving culture conditions by direct scavenging of free radicals.…”
Section: Discussionmentioning
confidence: 99%
“…However, the pregnancy and implantation rates are lower than those obtained with conventional IVF-embryo transfer, perhaps because, although more oocytes are recovered from PCOS patients, the derived oocytes and generated embryos tend to be of poorer quality (Plachot et al, 2003). Alternatively, the high oxidative stress resulting from increased lipid peroxidation and the chromosome aneuploidy that arises during extended culture for maturation in vitro could explain the lower pregnancy and implantation rates (Combelles et al, 2009;Harris et al, 2010;Requena et al, 2009). Interestingly, Tamura et al (2009) showed that intrafollicular melatonin concentration was significantly lower in PCOS patients than those in women undergoing IVF-embryo transfer, possibly accounting for the anovulation and poor oocyte quality seen in PCOS (Tamura et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…1 / JANUARY 2012 hyperandrogenemia (116). Indeed, it has recently been shown that differences in metabolism exist in oocytes derived from PCOS patients (117). Oocytes from PCOS patients are not likely to harbor an increased number of numeric chromosome abnormalities, but the disturbed metabolic profile of oocytes is associated with chromosomal predivision (i.e., premature separation of sister chromatids) (117).…”
Section: Abnormal Folliculogenesis and Implantationmentioning
confidence: 99%
“…Indeed, it has recently been shown that differences in metabolism exist in oocytes derived from PCOS patients (117). Oocytes from PCOS patients are not likely to harbor an increased number of numeric chromosome abnormalities, but the disturbed metabolic profile of oocytes is associated with chromosomal predivision (i.e., premature separation of sister chromatids) (117). During early pregnancy, the embryo may be exposed to androgen excess in utero, which may have long-term effects, particularly on female offspring.…”
Section: Abnormal Folliculogenesis and Implantationmentioning
confidence: 99%